A comparison of the cost-effectiveness of different eucalypt cut-stump control management options to reduce competition from coppice regrowth during stand establishment in Mpumalanga, South Africa. Issue 3 (3rd July 2018) - Roberts, Jonathan C; Little, Keith M; Light, Marnie E
Abstract : Selected cut-stump ( Cut_surface ) and basal frill ( Basal_frill ) treatments were tested on Eucalyptus macarthurii cut stumps that had previously been coppiced multiple times. Treatments included the application of herbicide (triclopyr as an amine salt, 360 g L −1 ), either to the cut-surface or to a basal frill (cuts made through the bark and into the cambium at the base of the tree). These treatments were integrated with non-chemical control methods, where seedlings were planted either between each stump row or within the row, to determine whether such treatments could further reduce the level of coppicing. Stump mortality for both the Basal_frill and Cut_surface treatments were equally effective, with 87% of the stumps killed when assessed at 14 weeks following initial treatment. No significant treatment differences were detected for the various growth variates of the stand at rotation end (stocking, basal area and volume). This can be attributed to a lack of competition from any coppice regrowth due to good control on each occasion. As there were no significant differences between the treatments, the Cut_surface treatment would be preferable due to the lower overall costs. However, for this method to be most effective, it is important that the herbicide be applied to the cut-surface of the felled tree within one day of felling. This may pose a safety issue, especially with mechanised felling of a stand. Further research on extending the period for application to the cut-surface could be beneficial. However, if reduced herbicide use is a prerequisite, coppice regrowth can be manually removed.